Zmowy przetargowe na przykładzie zamówień na roboty budowlane: Collusion during tender an example of construction work contracts - Rytel, Olga (Management and Administration Journal, 2021)
This paper describes the essence of collusion during tender (such collusion is illegal agreement restricting the effectiveness of the use of public funds). It shows examples of public procurement, which aroused suspicion that the companies entered into collusion to agree the level of prices of their offers.